P438 Gay, bisexual and other men who have sex with men prefer sexual health clinic nurses over family physicians for PrEP delivery. (14th July 2019) - Tan, Darrell; Chris, Allison; Schnubb, Alexandre; Knox, David; Wilton, James; Shahin, Rita; Chan, Arlene; Mishra, Sharmistha; Grace, Daniel; Rogers, Tim; Bayoumi, Ahmed; Maxwell, John; et al.
Abstract : Background: More providers are needed to deliver PrEP at scale. We examined intentions to seek PrEP from family physicians (FPs) and sexual health clinic nurses (RNs) within an implementation science study on decentralizing PrEP delivery to gay, bisexual and other men who have sex with men (gbMSM). Methods: Strategy A was a knowledge dissemination intervention in which community organizations distributed info-cards to gbMSM considering PrEP. Men used the cards to view an online module and meet with their FPs, who could use the card to complete an accredited e-module about PrEP. Strategy B was an implementation intervention in which gbMSM could instead access PrEP from sexual health RNs. Participants completed an optional survey at baseline and 6 months. We used descriptive statistics to characterize the sample and logistic regression to identify characteristics associated with intentions to seek PrEP from FPs vs RNs. Results: From 3013 cards distributed, 339 men accessed the module; 179 completed the baseline survey and are included in this analysis. Median (IQR) age was 31 (26, 40) years, 97.7% were cisgender males and 46.4% had a prior bacterial STI. Most (n=119, 66.5%) had a FP, of which only 59.5% were 'out' to them. Of 97 respondents with a FP and wanting to start PrEP, 35.1% vs 65.0% intended to use Strategy A vs B respectively (p=0.003). In univariable analyses, characteristics associated with intent to approach FPs included being 'out' to that doctor (OR=10.67, 95%CI=3.35, 33.96), very good/excellent physician skills in general communication (OR=3.42, 95%CI=1.38, 8.48) and participatory decision-making (OR=3.33, 95%CI=1.14, 9.79). In multivariable analysis, being 'out' was the only significant predictor (aOR=14.35, 95%CI=1.59, 129.83). Conclusion: Among gbMSM with a FP, sexual health clinic RNs were preferred over FPs for PrEP by most. Multiple strategies are needed to increase numbers of PrEP providers, including interventions to help gbMSM feel comfortable disclosing sexual orientation. Disclosure: No significant relationships.